Mutations inactivating mitochondrial genes in Chlamydomonas reinhardtii. (August 2001) - Remacle, C.; Duby, F.; Cardol, P.; Matagne, R. F.
Abstract : Chlamydomonas reinhardtii is now becoming a useful model for the study of mitochondrial genetics in a photosynthetic organism. The small (15.8 kb) mitochondrial genome C. reinhardtii has been sequenced completely and all the genes have been identified. Several mutants inactivated in mitochondrial genes encoding components of the respiratory complexes I, III and IV have been characterized at the molecular level. Assembly of complex I in several mutant strains and mapping of mitochondrial mutations by recombinational analysis are also described.